The Political Implications of Generational Demographic Change - Schultz, David (Socialinė teorija, empirija, politika ir praktika, 2026)
Demographic changes such as aging and fertility portend many things. They include impacts for labor and employment, pensions, and schooling. But do demographic changes implicate political change? A generation ago, American scholars examined racial demographic changes in the US and forecasted an ‘emerging Democratic majority’. This did not occur. But, since that prediction, the US as well as the rest of the world has experienced generational shifts, seeing the exiting of the pre-WWII and now the post-WWII or Baby Boomer generations and their replacement with the Millennials and Gen Z. Using the US as a case study, this paper examines the political impact which the shift in generations has had upon American politics, along with predictions regarding what this shift will mean for the immediate future. The thesis is that much of the conflict in US politics in the last twenty years has been driven in part by generation differences. Moreover, while there are generally significant generation differences in political attitudes in the US, such differences are not uniform, and they are mediated by race, class, and gender such that while there are possibilities for significant political change in terms of party composition and public policy, there is no guarantee regarding the exact direction.